2013
DOI: 10.1101/lm.030411.113
|View full text |Cite
|
Sign up to set email alerts
|

Activation of β2-adrenoceptor enhances synaptic potentiation and behavioral memory via cAMP-PKA signaling in the medial prefrontal cortex of rats

Abstract: The prefrontal cortex (PFC) plays a critical role in cognitive functions, including working memory, attention regulation, behavioral inhibition, as well as memory storage. The functions of PFC are very sensitive to norepinephrine (NE), and even low levels of endogenously released NE exert a dramatic influence on the functioning of the PFC. Activation of b-adrenoceptors (b-ARs) facilitates synaptic potentiation and enhances memory in the hippocampus. However, little is known regarding these processes in the PFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 76 publications
4
43
0
Order By: Relevance
“…To dissect the molecular pathways that could be downstream of clenbuterol, we measured levels of BDNF and related downstream molecules in the cerebellum, a brain region severely affected by the disease (39,40), of male KOv and KOt mice and their WT littermates (animals were injected daily with saline vehicle or 5 mg/kg clenbuterol from P14 to 8-9 wk of age). Clenbuterol-mediated activation of β2-adrenergic receptors in the brain is known to activate PKA, thereby phosphorylating and activating CREB (29,32). As predicted, due to the high relative abundance of β2-adrenergic receptors in the cerebellum (41), the ratio of activated to total CREB (pCREB/tCREB) was significantly increased after clenbuterol treatment (Fig.…”
Section: Igf1 Is Reduced In Mecp2 Mutant Mice Through a Mirna-mediatedsupporting
confidence: 66%
See 3 more Smart Citations
“…To dissect the molecular pathways that could be downstream of clenbuterol, we measured levels of BDNF and related downstream molecules in the cerebellum, a brain region severely affected by the disease (39,40), of male KOv and KOt mice and their WT littermates (animals were injected daily with saline vehicle or 5 mg/kg clenbuterol from P14 to 8-9 wk of age). Clenbuterol-mediated activation of β2-adrenergic receptors in the brain is known to activate PKA, thereby phosphorylating and activating CREB (29,32). As predicted, due to the high relative abundance of β2-adrenergic receptors in the cerebellum (41), the ratio of activated to total CREB (pCREB/tCREB) was significantly increased after clenbuterol treatment (Fig.…”
Section: Igf1 Is Reduced In Mecp2 Mutant Mice Through a Mirna-mediatedsupporting
confidence: 66%
“…Previous studies have observed deficiencies in adrenergic signaling in central respiratory centers (13,34), which are related to alterations in cyclic adenosine monophosphate (cAMP), protein kinase A (PKA), and cAMP response element-binding protein (CREB) phosphorylation (35) that are downstream of β2-adrenergic receptor signaling (29,36). Consistent with relatively normal early development, no significant changes in respiratory frequency were observed at 4 wk (Fig.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Studies on animal models lacking β 1 ARs or treated with selective β 1 AR agonists or antagonists revealed the critical role of this adrenergic receptor subtype in both synaptic plasticity and memory formation, with particular emphasis on retrieval (12)(13)(14). Genetic deletion of β 2 ARs results in impaired memory modulation by stress or corticosterone and impaired hippocampal plasticity, in agreement with a pharmacologically established role of β 2 ARs in amygdala-dependent memory modulation and its effect on hippocampal function and in prefrontal cortex (2,15,16). However, little is known about the role of hippocampal β 2 ARs in hippocampus-dependent longterm memory formation and processing.…”
supporting
confidence: 65%